The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4103/0975-7406.114305
|View full text |Cite
|
Sign up to set email alerts
|

Apexification with calcium hydroxide and mineral trioxide aggregate: Report of two cases

Abstract: The completion of root development and closure of the apex occurs up to 3 years after the eruption of the tooth. The treatment of pulpal injury during this period provides a significant challenge for the clinician. The importance of careful case assessment and accurate pulpal diagnosis in the treatment of immature teeth with pulpal injury cannot be overemphasized. The treatment of choice for necrotic teeth is apexification, which is induction of apical closure to produce more favorable conditions for conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…REPs began around 1952, when a German dentist called: Dr. B. W. Hermann advocated the use of calcium hydroxide as a dressing for after a vital pulp amputation (Hermann, 1952 ). Today, many dentists still use calcium hydroxide, mainly for apexification (Gawthaman et al, 2013 ), although MTA has overtaken calcium hydroxide to become the most popular pulp repair material (Monteiro et al, 2017 ). Subsequent REPs include the development of guided tissue or bone regeneration procedures and distraction osteogenesis (Jani, 1975 ); the application of platelet rich plasma (PRP) for bone augmentation (Kassolis et al, 2000 ); the use of platelet rich fibrin (PRF) for periodontal wound healing (Powell et al, 2009 ); and blood clot revascularization (BCR) by a Norwedgian dentist called Dr. Nygaard-Ostby for the regeneration of tissues within the root canals of pulpotimized teeth (Ostby, 1961 ; Nygaard-Ostby and Hjortdal, 1971 ).…”
Section: Introductionmentioning
confidence: 99%
“…REPs began around 1952, when a German dentist called: Dr. B. W. Hermann advocated the use of calcium hydroxide as a dressing for after a vital pulp amputation (Hermann, 1952 ). Today, many dentists still use calcium hydroxide, mainly for apexification (Gawthaman et al, 2013 ), although MTA has overtaken calcium hydroxide to become the most popular pulp repair material (Monteiro et al, 2017 ). Subsequent REPs include the development of guided tissue or bone regeneration procedures and distraction osteogenesis (Jani, 1975 ); the application of platelet rich plasma (PRP) for bone augmentation (Kassolis et al, 2000 ); the use of platelet rich fibrin (PRF) for periodontal wound healing (Powell et al, 2009 ); and blood clot revascularization (BCR) by a Norwedgian dentist called Dr. Nygaard-Ostby for the regeneration of tissues within the root canals of pulpotimized teeth (Ostby, 1961 ; Nygaard-Ostby and Hjortdal, 1971 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mineral trioxide aggregate (MTA) has been used as apical plug in non-vital teeth with incompletely formed roots ( 1 , 2 ). In this situation, the marginal sealing provided by MTA is better compared to other materials ( 3 , 4 ), and ex vivo studies have demonstrated improvement when the cement remains in contact with the phosphate buffered saline (PBS) ( 5 , 6 ) due to the formation of carbonate apatite at the cement-dentin interface ( 7 ), with tag-like structures which partially obliterates the spaces between material and dentin ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of our participants had large dental fillings that often included the root canals of permanent teeth. Considering the type of treatment intervention in such cases, i.e., apexogenesis or apexification, the closure of the apex before the predicted time is expected [24,25]. Therefore, in our study, the filled permanent teeth had already reached the final stage of development (stage 8), according to the DPR images.…”
Section: Discussionmentioning
confidence: 82%